KOMUNIKASI MASSA DALAM PERSPEKTIF ISLAM (Kajian Terhadap Alquran pada Ayat-ayat Tabayyun) - Mildad, Jamal (Universitas Teuku Umar, 2016)
Tabayyun an understanding something carefully the information received from the media information, checked first against, correctness content of information, whether news and information contained elements of slander and pitting. Study uses library research approach, namely study of literature, where the collection of materials and research data conducted through the review of Qur'anic text, commentary and other references that support and are considered important in this study. In the Qur'an, tabayyun explicitly mentioned in Surat an-Nisa 'verse 94 and Al-Hujarat paragraph 6. From second verse, it is explained about tabayyun which means it is seeking to clarify the nature of things or truth of facts carefully and cautiously. The fall in this verse to teach the Muslims to becareful in receiving news and information. For information very decisive decision-making mechanism, even the decision of entity itself. When you look at the phenomenon of reports in the popular media today, both print and electronic, in the context of tabayyun us by letter of An-Nisa 'verse 94 and Al-Hujarat verse 6, God does’nt memperintahkan us to deny news of fasiq or accept it, because it could be the news true or false. Therefore shall researched in advance so that we don’t regret our lack of prudence. Keywords:Mass Communication, Islam, Tabayyun